1985
DOI: 10.1136/bmj.290.6464.275
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised controlled clinical trial comparing somatostatin and vasopressin in controlling acute variceal haemorrhage.

Abstract: References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
2
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(49 citation statements)
references
References 15 publications
4
36
2
7
Order By: Relevance
“…[6][7][8]10,12,13 It has been demonstrated that bolus injections of SMT cause a rapid and more pronounced reduction of portal pressure and azygos blood flow than those observed with continuous infusion. 26 These marked hemodynamic effects may explain, at least in part, the higher efficacy reported in clinical trials using additional boluses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8]10,12,13 It has been demonstrated that bolus injections of SMT cause a rapid and more pronounced reduction of portal pressure and azygos blood flow than those observed with continuous infusion. 26 These marked hemodynamic effects may explain, at least in part, the higher efficacy reported in clinical trials using additional boluses.…”
Section: Discussionmentioning
confidence: 99%
“…4 One placebo-controlled trial failed to show any beneficial effect with SMT, 5 although the high spontaneous success rate observed with placebo suggests that some inadvertent bias could occur in this study. 5 Furthermore, several randomized, controlled trials have shown that SMT is more effective than placebo, 6 and as effective as vasopressin, 7,8 vasopressin associated with nitroglycerin, 9 terlipressin, 10,11 and balloon tamponade, 12,13 with fewer side-effects in most of these studies. Both SMT and octreotide, a synthetic SMT analogue, have shown an efficacy similar to that of EST for the control of acute variceal bleeding, [14][15][16][17] and for the prevention of early rebleeding, 18 while morbidity significantly decreased.…”
mentioning
confidence: 99%
“…Estudos realizados (26,27,32,34,36,40) têm demonstrado que a somatostatina ou seu análogo sintético, o octreotide, é tão eficaz quanto a escleroterapia, tratamento considerado padrão na maioria dos centros médicos, no controle da HDA por ruptura de varizes esofágicas ou na prevenção do ressangramento precoce (17) . Deve-se, no entanto, ressalvar o fato de que o octreotide parece não ter a mesma eficácia que a somatostatina (2,4,9) .…”
Section: Discussionunclassified
“…As complicações foram significativamente mais freqüentes (19% x 9%) e mais graves no grupo da escleroterapia. A despeito de JENKINS et al (26) , em avaliação inicial, encontraram dados que se superpõem aos anteriores, quando avaliaram maior casuística (27) e obtiveram controle do sangramento em 48 h (85% no grupo do octreotide e 82% no da escleroterapia) e mortalidade em 5 dias semelhantes, porém observaram maior mortalidade (31% x 17%) em 60 dias e número maior de complicações no grupo do octreotide, embora sem significância estatística.…”
Section: Discussionunclassified
See 1 more Smart Citation